(untitled) - The World Bank (Washington DC, 2009)
Africa Development Indicators 2008/09 provides the most detailed collection of data on Africa available in one volume. It contains more than 450 macroeconomic, sectoral, and social indicators, covering 53 African countries. Additional data may be found on the companion CD-ROM, covering about 1,400 indicators from 1965 to 2006. A few macro indicators have provisional data for 2007 while others indicators have data for 2007 2008. Designed to provide all those interested in Africa with a focused and convenient set of data to monitor development programs and aid flows in the region, this is an invaluable reference tool for analysis and policy makers who want a better understanding of the economic and social developments occurring in Africa.
Keywords: Social indicators,Chỉ báo xã hội; Africa,Châu Phi